PERISTIWA-PERISTIWA YANG MEMBUAT BAHAGIA - Harmaini Harmaini; Alma Yulianti (Psympathic : Jurnal Ilmiah Psikologi, 2014)
This research aimed to explore the events that experienced and made the teens happy. The survey method was conducted with a total sample of 51 boys and 159 girls of high school students in Pekanbaru City. The instrument was an open-ended question and the data processed by descriptive analysis. Based on the research results, the three major components that events make teens happy namely (1) Relation by 55.7% includes events related to parents, family and peers. (2) Personal affective by 34.7% of the events associated with the opposite sex, affection, the psychological benefits, hobbies, etc., and (3) achievement by 24.7% includes events associated with achievement, graduation, ability to complete the task, and satisfactory result.